2018
DOI: 10.3390/nu10121905
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Dietary Intake and Adherence to the NU-AGE Diet Following a One-Year Dietary Intervention among European Older Adults—Results of the NU-AGE Randomized Trial

Abstract: Background: The Mediterranean Diet has been proposed as an effective strategy to reduce inflammaging, a chronic low grade inflammatory status, and thus, to slow down the aging process. We evaluated whether a Mediterranean-like dietary pattern specifically targeting dietary recommendations of people aged over 65 years (NU-AGE diet) could be effective to shift dietary intake of older adults towards a healthful diet. Methods: Adults aged 65–80 years across five EU-centers were randomly assigned to a NU-AGE diet g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 52 publications
3
59
0
2
Order By: Relevance
“…However, we observed that, across the study, increasing adherence to the diet was associated with an attenuated loss of microbiome diversity (table 1). For a finer detailed microbiota–diet association analysis, we used adherence scores to the MedDiet, previously calculated based on the NU-AGE Food Based Dietary Guidelines (FBDG) 35. These are recommendations that act as the basis for facilitating or measuring adherence to healthy eating initiatives or dietary interventions for improving public health.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we observed that, across the study, increasing adherence to the diet was associated with an attenuated loss of microbiome diversity (table 1). For a finer detailed microbiota–diet association analysis, we used adherence scores to the MedDiet, previously calculated based on the NU-AGE Food Based Dietary Guidelines (FBDG) 35. These are recommendations that act as the basis for facilitating or measuring adherence to healthy eating initiatives or dietary interventions for improving public health.…”
Section: Resultsmentioning
confidence: 99%
“…These are recommendations that act as the basis for facilitating or measuring adherence to healthy eating initiatives or dietary interventions for improving public health. The NU-AGE FBDG covered 15 dietary goals including a vitamin D supplement that has been described in detail by Berendsen et al 35. We created Random Forest (RF) models to predict dietary adherence from microbiome profiles at both the baseline and final (1-year) time points.…”
Section: Resultsmentioning
confidence: 99%
“…Macronutrient intakes and the amount of dietary FI were retrieved and averaged per day. In addition, adherence to healthy dietary patterns was obtained using the NU-AGE Food Based Dietary score (Mediterranean-type diet) [35]. Participants having a protein intake above 1.1 g/kg of body weight were classified as meeting the recommended amount of protein intake for older people [36].…”
Section: Assessment Of Dietary Intakementioning
confidence: 99%
“…[11]. В частности, для изучения возможностей средиземноморской диеты влиять на возрастные изменения метаболизма, на состояние микробиоты и когнитивные особенности у пожилых пациентов проведено масштабное исследование «Проект NU-AGE», в которое было включено более 1000 человек [12]. Как известно, средиземноморская диета характеризуется оптимальным соотношением жирных кислот омега-6 и омега-3, полифенолов и других антиоксидантов, включает повышенное потребление пребиотической клетчатки и углеводов с низким гликемическим индексом, а также предпочтительное потребление растительных (вместо животных) белков.…”
Section: связь микробиота-кишечник-мозгunclassified
“…Как известно, средиземноморская диета характеризуется оптимальным соотношением жирных кислот омега-6 и омега-3, полифенолов и других антиоксидантов, включает повышенное потребление пребиотической клетчатки и углеводов с низким гликемическим индексом, а также предпочтительное потребление растительных (вместо животных) белков. По результатам исследований, средиземноморская диета способствовала увеличению Bifidobacteria и общего количества короткоцепочечных жирных кислот, и расценена авторами как эффективная стратегия для уменьшения хронического воспаления и, следовательно, для замедления процесса старения [11,12].…”
Section: связь микробиота-кишечник-мозгunclassified